Surgical Management of Esophageal Achalasia in Pediatrics: A Systematic Review - Goneidy, Ayman; Cory-Wright, James; Zhu, Limeng; Malakounides, Georgina (European Journal of Pediatric Surgery, 2020)
Introduction There are no evidence-based guidelines on the surgical management of esophageal achalasia (OA) in children. This can be a challenging condition with significant physical and psychological morbidity. Our aim was to identify the most common management modalities and their outcomes.Materials and Methods A systematic review was performed through a literature search of health care databases in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, aiming at identifying pediatric series discussing the diagnosis and management of OA. Duplicates, case series with < 9 patients, and follow-up of < 1 year were excluded. The included papers were analyzed for diagnostic methods, primary treatment method, complications, follow-up duration, outcome measures recorded, and outcome.Results Data from 33 papers for 742 children treated for OA was analyzed. Eleven mentioned multiple management modalities. In summary, 25 described Heller's esophagomyotomy (HM), 13 esophageal dilatation (EOD), and 6 peroral esophageal myotomy (POEM). Mean follow-up was 43.7 months (12–180). Outcome measures were heterogeneous. However, analysis of reported success showed a mean success of 78% for HM (p = 1.79 × 10–7), 44.9% for EOD (p = 0.24), and 99.3% for POEM (p = 0.001). Reported complications were 12.8% for HM, 5% for EOD, and 24.4% for POEM. Further interventions were required for 10.9% of HM, 62.3% of EOD, and 0.01% of POEM patient groups.Conclusion Methods of diagnosis and measures of successful outcomes were heterogeneous, limiting the strength of evidence. HM showed superior short-term success rates to EOD. POEM is a promising modality but requires investment in equipment and training. Information about sustainability of response and long-term outcomes is lacking.
Keywords: achalasia; Heller; children; management